161k views
1 vote
Solve the equation below for x. -1 2(3x - 4) = 11

2 Answers

5 votes

Answer:

x= 37/36

Explanation:

−12(3x−4)=11

Step 1: Simplify both sides of the equation.

−12(3x−4)=11

(−12)(3x)+(−12)(−4)=11(Distribute)

−36x+48=11

Step 2: Subtract 48 from both sides.

−36x+48−48=11−48

−36x=−37

Step 3: Divide both sides by -36.

−36x

−36

=

−37

−36

x=

37

36

Answer:

x=

37

36

User Elektito
by
5.8k points
4 votes

-1/2(3x-4) = 11

Multiply both sides by -2:

3x-4 = -22

Add 4 to both sides:

3x = -18

Divide both sides by 3:

X = -6

User Ewanc
by
5.6k points